Virtual Police in the Indonesian Constitutional System: A Restorative Justice Approach to Cybercrime Prevention (An Empirical Study in Sambas Regency) - Saliro, Sri Sudono; Aminah, Siti; Jamaludin, Jamaludin; Aprilsesa, Tri Dian; Kusryat, Dheanita (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The Virtual Police Approach as Restorative Justice Prioritizes Preventive Efforts. Indeed, there is a close relationship between preventive policing and crime prevention. Preventive policing is part of crime prevention; however, crime prevention encompasses a broader scope than preventive policing alone. This study aims to analyze the implementation of virtual police within the Indonesian constitutional system as part of cybercrime prevention efforts, as regulated in the Electronic Information and Transactions Law (UU ITE), and to describe the effectiveness of virtual police in this context. This research employs a qualitative method and is classified as empirical legal research, utilizing both normative legal and descriptive-analytical approaches. Data were obtained through interviews and observations, using purposive sampling techniques. The results of the study reveal that the implementation of virtual police is a manifestation of the enforcement of the Electronic Information and Transactions Law (executive function) as a legal effort to prevent cybercrime. The presence of virtual police as law enforcers has made cybercrime prevention more effective, supported by a strong legal framework. However, challenges remain in the form of societal legal culture, particularly the public's lack of awareness and compliance in the digital space.